Organoleptic Quality of Salted Quail Eggs Using Boiled Salt From Brebes - Muhamad Hasdar; Yunika Purwanti; Nurwati Nurwati (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2021)
Salted eggs are one of the popular products and are liked by the people of Indonesia. Processing salted quail eggs is an effort for preservation, in addition to improving the taste of quail eggs This study aims to determine the organoleptic quality of quail eggs salted with fine boiled salt with a concentration of 20% (w/w) and 30% (w/w). The incubation time for the salting process is 4 days. organoleptic test with 60 untrained panellists. Yolk colour quality produces a slightly yellow colour (p>0.05). The aroma of salted quail eggs is slightly fishy (p>0.05). Taste quality has a difference (p<0.05) where the 20% salt concentration treatment produces a bit less salty, while the 30% salt concentration treatment produces a slightly salty taste. The tasting test did not have a difference between treatments (P>0.05) which produced unsubstantiated eggs, and the panellists' organoleptic test on average resulted in a preference for the 30% salt concentration treatment.